THE ROLE OF TRADITIONAL CHILDREN'S STORIES IN CHARACTER DEVELOPMENT IN THE GLOBAL ERA FOR THE STUDENTS OF ELEMENTARY SCHOOL - Ch. Evy Tri Widyahening (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
this era of globalization and increasingly sophisticated technology, literature is not only seen as a part of art and culture that aims to entertain but is a means of learning language, studying history, developing character, and so on. Literature has become an important part of education. One of the objectives of literature, especially related to traditional children's literature in education, is to internalize the character values seen in the daily life of society, especially elementary school students. The rapid development of the internet and followed by increasingly sophisticated technological developments has influenced the lifestyle and character of most elementary school students. Coupled with the condition of the corona pandemic and all activities carried out at home, surfing activities on the internet are increasingly out of control. This is very worrying because the flow of information displayed on the internet and offers of online games, which are not all safe for children, are milling about on the internet and these things can affect the character of children, especially children in elementary schools. To overcome this, the role of children's stories as part of literature can be used in developing student character to be better because the stories displayed contain very good moral values. The role of teachers and parents is also very important to overcome the impact of the internet on elementary school students, namely through storytelling activities. With storytelling activities, students can learn various characters contained in children's stories. The purpose of writing this article is the existence of problems related to the decline in the level of community morality, especially students in elementary schools during the corona pandemic which is due to uncontrolled internet use. One solution that can be done is to strengthen the understanding of character education through traditional children's stories told by teachers and parents to students in elementary schools. Keywords: Traditional Children's Stories, Literature, Character Education, Internet.